Development of 'NumBiz Kidz' Mobile Game Based on MSME Context of Tembokrejo Broiler Chicken to Enhance Early Childhood Numeracy Literacy - Mufidatul Ilmiyah; Rani Darmayanti; Maulid Datul Hasanah; Paulo Vitor da Silva Santiago; Kalim Ullah (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2026)
Numeracy literacy is a fundamental skill for early childhood to understand basic quantitative concepts relevant to daily life, including simple entrepreneurial contexts that foster an entrepreneurial mindset from an early age. However, conventional learning methods often fail to connect abstract mathematical concepts with practical, engaging applications, necessitating the development of innovative learning media. This study aims to conduct the initial development stage of an educational mobile game called